Burnout syndrome in nursing residents in COVID-19 pandemic - Stephanie Jully Santos de Oliveira; Wallace Ferreira da Silva; Tais Veronica Cardoso Vernaglia; Silvana Vieira das Chagas; Cristiane Rodrigues da Rocha (Universidad de Santander, 2023)
Introduction: The incidence of Burnout Syndrome (BS) among nurses is higher. For this group, nursing residents undergo periodic assessments regarding compliance with the care workload in closed sectors, such as Intensive Care and Emergency Care, that put them at higher risk for the syndrome. Objective: Identify the prevalence and related factors for BS in nursing residents. Material and Methods: Quantitative, analytical, cross-sectional study with 106 nurses enrolled in the Residency program in Rio de Janeiro, Brazil, based on the following instruments: Maslach Burnout Inventory-General Survey Scale and an occupational sociodemographic questionnaire. Non-parametric statistical tests for independent samples were applied and Mann-Whitney test 15 was used for quantitative variables. Results: The results show that variable changes in relationships indicates stage 4 of the BS when compared to the other stages. For the other variables, there were no statistically significant differences. Discussion: Studies reveal that work-family balance is closely related to how job satisfaction is affected and mitigates the negative effects of BS. Conclusions: Consequences on relation patterns are among the most affected symptoms in the lives of nursing residents. This study is expected to contribute to raising awareness of the problem in question and to improve the quality of work life of resident nurses, detecting and preventing their illness